TOURISM DEVELOPMENT ANALYSIS DURING THE COVID-19 PANDEMIC IN THE SPECIAL REGION OF YOGYAKARTA - Rini Raharti; Nurwiyanta Nurwiyanta; Joko Purwanto Nugroho; Faiza Az Zahra Septiadewi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The tourism sector is one sector that significantly contributes to regional income to improve economic development. The Covid-19 outbreak has resulted in a decline in the DIY tourism sector, causing the economy to experience a downturn. The undiscovered Covid-19 virus has added to the public's anxiety for activities. For this reason, the government needs to take policies related to how to make efforts in the form of tourism development strategies during the pandemic. The Covid-19 pandemic is an epidemic that changes the order of people's lives worldwide or is called the new normal. People are required to live in a new normal to maintain the health and safety of their souls. The objectives of this study are a) To analyze the DIY tourism development strategy during the Covid-19 pandemic; b) to know the strategies carried out by stakeholders in carrying out tourism recovery in DIY. This study uses qualitative research methods, which research is based on the collection, analysis, and interpretation of power in the form of a visual narrative. Based on the results of the discussion and conclusions in this study regarding the strategy for developing destinations in the Special Region of Yogyakarta, recommendations that need to be conveyed in developing existing tourism products, maximizing the tourism market and other potentials that support this strategy by developing tourism destinations with sustainable principles from environmental aspects, socio-cultural and economic, as well as easily accessible and attractive to tourists, designing tourism marketing that can increase tourist visits, developing competitive tourism industry and creative economy, developing organizations, human resources, regulations and operational mechanisms that are effective and efficient.